Animal Nutrition and Productions: Series II (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
The externalization of animals’ genetic potential is determined by a number of external factors, of which feeding plays a major role. Animal nourishment is one of the most important levers in ensuring the efficiency of animal production due to both the high share of feed costs in the total cost of products and the influence this has on the growth, reproduction, and health of animals, as well as the quality of products obtained from them. This particular field is one of the most dynamic in the field of husbandry sciences due to the continuous acquisition and use of numerous results obtained from studies on energy metabolism and nutrients, related to the composition of feed and its influence on animal products. This is also due to the great advances made in genetics with the creation of new types of animals with increasing productive potential and different food requirements. The following Special Issue is dedicated to interdisciplinary studies on animal nutrition, physiology, chemistry, biochemistry, genetics, reproduction, and breeding technologies. The articles contained herein cover a wide range of topics related to feed quality, the influence of food on production levels, the quality of production, and their influence on animal health.